Mineralogy in the estimation of the temperature of forest fire and their immediate effects in Andosols, State of Mexico - Hernández Vallecillo, Gabriel Alejandro; Gutiérrez Castorena, Ma. del Carmen; Barragán Maravilla, Sandra Monserrat; Ángeles Cervantes, Efraín Reyes; Gutiérrez Castorena, Edgar Vladimir; Ortiz Solorio, Carlos Alberto (Instituto de Ecología, A.C., 2020)
Fire is a natural phenomenon and indispensable within the biogeochemical cycles of soils, especially those that sustain a forest vegetation as in the case of Andosols. Nevertheless, little is known about the temperatures that are reached in the soils in forest fires, and their immediate effect on their edaphic properties. In April 2017, field trips were conducted in San Pablo Ixayoc, Texcoco, State of Mexico, two days after the start of the forest fire. Composite and unaltered soil samples in the first 5 cm of soil were collected for the analysis of their edaphic and micro-morphological properties. The estimation of the temperature was made through a thermal experiment and mineralogical analysis. Based on the destruction, formation and dominance mainly of the oxides, ferromagnesian and pseudo-sands, the temperatures reached in the forest fires can be grouped in: < 250 °C for superficial and crown fires in Quercus sp. and Pinus sp., and 250 °C - 500 °C in fallen trees and tree roots that continued to be incinerated. The MO, pH, CIC, P, K+ and Na+ and texture show direct and indirect tendencies according to the type of ashes and temperature and not with the severity and type of vegetation. Surface and crown fires immediately modified Andosols' properties and improved their quality, while, at those points where higher temperatures were reached, the soil is affected but there is less impact because fires occur in specific and small areas.